2019
DOI: 10.1590/1980-5373-mr-2019-0127
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Surface Integrity of Wire Electrical Discharge Machining of Thin Ti6al4v Plate Using Coated and Uncoated Wires

Abstract: Wire Electrical Discharge Machining (WEDM) is one of the most important production technologies to manufacture very accurate small components and tools on any electrical conductive material. Titanium and its alloys have been widely used in automobile and aerospace industry as well as in medical engineering field. Small components and tools with complex geometrical shapes are difficult to be produced on titanium alloys by both conventional and nonconventional machining technologies. In this work an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The fuzzy model was able to predict the process outcomes effectively. Amorim et al 10 studied the effect of zinc coated wire on WEDM of Ti6Al4V alloy. The zinc coating increased the IEG and enabled better flushing improved MRR.…”
Section: Powder Mixed Edmmentioning
confidence: 99%
“…The fuzzy model was able to predict the process outcomes effectively. Amorim et al 10 studied the effect of zinc coated wire on WEDM of Ti6Al4V alloy. The zinc coating increased the IEG and enabled better flushing improved MRR.…”
Section: Powder Mixed Edmmentioning
confidence: 99%
“…The Wire-cut Electrical discharge machining is one of the micro-machining process to cut the hard materials without demaging surfaces (Amorim et al 2019). After ISO-14000 implementations in materials processing industries, eco-friendly manufacturing methods have been proposed to minimize environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Chalisgaonkar et al [12] have carried out the two different techniques for material removal rate and surface roughness for the characteristics of the machined surface using the principle of WEDM on the titanium alloy. Amorim et al [13] concluded that the zinc-coated wire produced a better material removal rate and surface integrity at a higher wire feed rate when compared to the brass tool. Srinivasan et al [14] have concluded that TOPSIS optimization is one of the best multicriterion decision-making criteria.…”
Section: Introductionmentioning
confidence: 99%